OPTIMALISASI PENANGGULANGAN PUNGUTAN LIAR OLEH DIREKTORAT RESKRIM KHUSUS KEPOLISIAN DAERAH SUMATERA BARAT - Purba, Binsar Henson (LPPM Universitas Ekasakti Padang, 2019)
National extortion measures are regulated in the Republic of Indonesia Presidential Regulation Number 87 of 2016 concerning the Task Force for Clean Sweep of Illegal Levies. In West Sumatra, based on the West Sumatra Governor Decree number 0710-1247-2016, a Saber extortion team was formed. Various efforts have been made by the West Sumatra Regional Police Ditreskrimsus in tackling illegal levies both repressively and preventively, but still need to be optimized again. This research specification is Descriptive Analysis. The efforts made by the West Sumatra Regional Police Ditreskrimsus in tackling illegal levies are pre-eminent by instilling good values ​​/ norms so that these norms are internalized in a person. Furthermore, it is a preventative effort by conducting socialization to community service offices, making billboards / banners about illegal levies; and giving appeals to the public and repressive actions by taking legal action against illegal payments which are indicated as criminal acts. optimizing the role of the Ditreskrimsus Regional Police of West Sumatra in tackling illegal levies is done by increasing the capacity of the police organization's resources and the Criminal Policy approach in the form of a reasoning and non-reasoning policy.